Twin-to-Twin Transfusion Syndrome—30 Years at the Front - De Lia, Julian E.; Kuhlmann, Randall S. (American Journal of Perinatology, 2014)
Thirty years ago, twin-to-twin transfusion syndrome (TTTS) was one of the most challenging problems of modern obstetrics. The associated mortality and morbidity was staggering, and a sense of hopelessness prevailed among clinicians and pediatric pathologists. Technical advances in ultrasound, endoscopy, video recording, and medical lasers formed the basis for diagnosis and in utero therapy of placental disorders. We review some historical events which gave rise to a new treatment modality for TTTS, fetoscopic laser occlusion of chorioangiopagous vessels, now the most common operation performed worldwide in behalf of fetuses in peril.
Keywords: monochorionic twins; twin-to-twin transfusion syndrome; FLOC